Exploring the time-resolving capabilities of XIDer assemblies - Williams, Morag; Busca, Paolo; Collonge, Michael; Fajardo, Pablo; Fischer, Paulina; Martin, Thierry; Ritzert, Michael; Ruat, Marie; Schimansky, David (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2023)
The XIDer R&D project, between the European Synchrotron Radiation Facility (ESRF) and Heidelberg University, is developing state-of-the-art detectors for the high-energy, high-flux beamlines of the ESRF Extremely Brilliant Source (EBS). In particular, the XIDer detector aims to tackle the significant challenges posed by time-resolved experiments analysing the pattern of diffracted or scattered X-rays. To fulfil the needs of these experiments, a novel on-chip incremental digital integration readout scheme with per-pixel digital data output has been implemented. The EBS beam operates with different time structures: from a near-100% duty cycle X-ray beam to an up to 5.7MHz pulsed X-ray beam. For the latter EBS mode, the XIDer ASIC has been designed to have a fast front-end and memory storage cells, such that the pulsed EBS beam can be exploited by time-resolved experiments. Recent measurements of the time-resolving capabilities of XIDer ASICs hybridised cadmium telluride and cadmium zinc telluride sensors are presented.
Gesehen am 26.08.2024
Online verfügbar: 25 September 2023